2000
DOI: 10.1080/713688302
|View full text |Cite
|
Sign up to set email alerts
|

The Disinvestment of Public Sector Enterprises: The Indian Experience

Abstract: This paper examines the disinvestment of shares of public sector enterprises (PSEs) in India since 1991. The poor performance of PSEs made reform increasingly urgent in the context of the broader strategy of the liberalization of the economy to deal with the perceived weaknesses of India's development strategy. The paper argues that the main aim of disinvestment has been to reduce the public sector borrowing requirement, at the cost of the restructuring and rationalization of PSEs in particular and the public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…In India, the economic reform in general, and financial sector reform in particular is seen as threatening the material interests of various interest groups such as politicians, civil servants, organised labour etc. During the pre-reform period, the public sector institutions provided these pressure groups with resources to distribute in terms of jobs, funds and status and allowed them to control a wide range of activities (Arun and Nixson, 2000). Naturally these pressure groups may not be sympathetic to reform process and this necessitates the building of a consensual approach to reforms prior to implementation and/or during the course of the reforms.…”
Section: The Gradualist Approach To Financial Reformmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, the economic reform in general, and financial sector reform in particular is seen as threatening the material interests of various interest groups such as politicians, civil servants, organised labour etc. During the pre-reform period, the public sector institutions provided these pressure groups with resources to distribute in terms of jobs, funds and status and allowed them to control a wide range of activities (Arun and Nixson, 2000). Naturally these pressure groups may not be sympathetic to reform process and this necessitates the building of a consensual approach to reforms prior to implementation and/or during the course of the reforms.…”
Section: The Gradualist Approach To Financial Reformmentioning
confidence: 99%
“…: 1991-2000 The broad thrust of the economic reforms in India is not very different from the changes being implemented in other developing countries and in the erstwhile socialist world in that it is aimed towards enhancing the productivity and efficiency of the economy as a whole, and also increasing international competitiveness (Arun, 1999). The reform programme involves a move away from centralised allocation of resources in some key sectors by the government to allocation by market forces (Arun and Nixson, 2000). As a major component of economic reforms, reforms in the financial sector are aimed at improving the allocative and functional efficiency of the financial system and developing a diversified competitive financial system to support the development and growth of the real sector.…”
Section: The Gradualist Approach To Financial Reformmentioning
confidence: 99%
“…There are a large number of studies that discuss the performance of PSUs in the Indian context. But very few of these use rigorous techniques and are therefore largely descriptive (Arun & Nixson, 2000;Mathur, 2010;Nagaraj, 2005;and Trivedi, 1990). Some of the most prominent rigorous studies (e.g., Gupta, 2006Gupta, , 2011 showed that disinvestment (even the sale of minority shares) had a positive effect on PSU financial performance, ostensibly because new owners injected greater commercial drive, which helped improve A.…”
Section: Earlier Studies On Psu Performance In India and The Proposedmentioning
confidence: 99%
“…Public sector enterprises were mostly the outcome of political considerations and bureaucratic rent-seeking which constrained the choices on size, technology and location of these institutions in a competitive regime. The poor performance of these enterprises, which was manifested in low or negative returns to public investment, raised concerns about the rationale of supporting these enterprises as an engine of growth (Arun and Nixson, 2000).…”
Section: Development Strategies and Regulatory Legislations 1947-1991mentioning
confidence: 99%
“…The disinvestment of government shareholdings in the equity of selected public sector undertakings is an important step towards wider private sector participation in economic development. The shift in attitude was interpreted as a belated realisation by government of the poor performance of public enterprises, and the new policies were intended to bring market discipline and public accountability to the performances of public enterprises by broad basing their management and ownership patterns (Arun and Nixson, 2000). The need for regulation of economic activities is often justified as a policy instrument to minimise the effects of market failures.…”
Section: Reforms Regulation and Competition Policymentioning
confidence: 99%